Employability of an ageing workforce in Bavaria/Germany - Conrads, Ralph (2005)
INIFES takes part in the Smart Region Project with research and transfer activities in two regions in the south of Bavaria/Germany. In contrary to our colleagues from the SÕSTRA-Institute, Berlin, working in the “New Lãnder” with high unemployment rates, these two regions were systematically selected among those Bavarian regions with relative better labour market performance. Further criteria for selection were a high heterogeneity within these regions in the dimensions of a) economic structure (importance of production activities) and b) demographic change (age structure of people between 15 and 65). As a result six districts (“Landkreise”) in the south and the west ofBavaria were selected (see figure 1).